Organization and Administration of Graduate Studies in Canadian Universities - Holdaway, Edward A. (Canadian Journal of Higher Education, 1994)
Considerable concern exists in Canada, the United States, and some other west- ern countries about the rates of non-completion of graduate programs and the increasing amount of time needed for completion. A 1990-91 study obtained information and opinions about graduate program practices from samples of department heads and experienced supervisors of graduate students in five Canadian universities. Aspects associated most with successful completion within the universities’ time limits were high student motivation, appropriate supervision, careful selection of students, clear definition of research field, and a substantial period of full-time study. The most commonly mentioned reasons provided for non-completion were acceptance of employment prior to comple- tion, inadequate supervision, financial constraints, ill-conceived projects, lack of motivation, and lack of ability.